Determination of GaN solubility in supercritical ammonia with NH4F and NH4Cl mineralizer by in situ x-ray imaging of crystal dissolution - Schimmel, Saskia; Lindner, Michael; Steigerwald, Thomas; Hertweck, Benjamin; Richter, Theresia M.M.; Künecke, Ulrike; Alt, Nicolas; Niewa, Rainer; Schlücker, Eberhard; Wellmann, Peter (Journal of Crystal Growth, 2015)
Quantitative data on the solubility of GaN in supercritical ammonia using NH4F as mineralizer are reported. The solubility is determined by in situ x-ray imaging of the dissolution of GaN single crystals. First, solubility values obtained by this method with NH4Cl as mineralizer are presented and discussed with respect to existing literature data Monitoring the dissolution process in situ reveals the time when the solubility limit is reached. Thus, it allows to distinguish the saturation of the solution from dissolution based on mass transport and deposition. This is a key advantage of solubility measurements by in situ x-ray imaging compared to gravimetric methods. Our results indicate that the solubility limit is reached much faster than usually assumed in gravimetric solubility studies and the solubility of GaN in ammonothermal media is significantly lower than reported so far. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Solubility; Solvents; Mineralizers; Growth from solutions; Ammonothermal crystal growth; Nitrides